2004
DOI: 10.1097/01.coc.0000135567.62750.f4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Merkel Cell Carcinoma

Abstract: Purpose: The purpose of this study was to evaluate the treatment of Merkel cell carcinoma. Materials and Methods: We reviewed 85 cases of Merkel cell carcinoma. There were 68 males and 17 females. The majority of cases involved head and neck sites (48%), followed by the extremities (38%) and trunk (14%). Sixty-seven percent of the patients had stage I disease that was localized to the skin of origin at presentation. Twenty-five percent and 8% were stage II (nodal metastasis) and stage III (distant metastasis),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
69
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(77 citation statements)
references
References 46 publications
3
69
1
4
Order By: Relevance
“…Most studies have shown the disease stage to be the most important prognostic factor for MCC [3, 4, 9,10,11,12,13]. In the study by Fenig et al [11], patients with local disease achieved longer 3-year OS compared with patients with locoregional disease (80 vs. 22%).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies have shown the disease stage to be the most important prognostic factor for MCC [3, 4, 9,10,11,12,13]. In the study by Fenig et al [11], patients with local disease achieved longer 3-year OS compared with patients with locoregional disease (80 vs. 22%).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly one-third of patients die within three years from the time of diagnosis. 12 Unfavorable prognostic factors include male gender, age more than 65 years with co-morbid diseases, distant metastatic disease, tumor of head and neck region, tumor size more than 2 cm in diameter, tumor with more than 10 mitoses per high-power field, evidence of vascular invasion, absence of an inflammatory reaction, and high expression of Kiel (Ki)-67 (proliferation index marker). 4,13 Lymph node involvement decreases survival from 88% to 50% and it shows within two years in 50% to 70% of all patients.…”
mentioning
confidence: 99%
“…Surgery alone has very high local recurrence rates for this disease. 12,13 Wide surgical resection taking http://mji.ui.ac.id 3 cm margin and 2.5 cm dept is sufficient, but some authors advocate less than 2-3 cm in case of 1.5-2 cm tumor without high local recurrence. An alternative to wide local resection is Mohs micrographic surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations